Chocolate dreams - Perelman, Helen; Waters, Erica-Jane (New York : Aladdin, 2010)
As spring arrives in the Candy Kingdom, Cocoa the Chocolate Fairy is honored to be selected to make the chocolate eggs for the royal parade, but a selfish troll has other plans.
3.9
K-3
K-3.
570
Keywords: Fairies -- Juvenile fiction; Candy -- Juvenile fiction; Chocolate -- Juvenile fiction; Fairies -- Fiction; Candy -- Fiction; Chocolate -- Fiction; Fairies -- Fiction; Candy -- Fiction; Chocolate -- Fiction